Single-Spore Extraction for Genetic Analyses of Arbuscular Mycorrhizal Fungi - Redecker, Dirk (Methods in molecular biology (Clifton, N.J.), 2020)
Biomass of arbuscular mycorrhizal fungi (AMF, Glomeromycota) is often only available in small quantities as these fungi are obligate biotrophs and many species are difficult to cultivate under controlled conditions. Here, I describe a simple, efficient approach to produce crude extracts from single or a small number of spores that can be used for genotyping AMF.